2016
DOI: 10.1007/s10096-015-2565-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microbiological samples in the hospital management of community-acquired, nursing home-acquired and hospital-acquired pneumonia in older patients

Abstract: We investigated the positivity rate, the detection rates for non-covered pathogens and the therapeutic impact of microbiological samples (MS) in community-acquired pneumonia (CAP), nursing home-acquired pneumonia (NHAP) and hospital-acquired pneumonia (HAP) in elderly hospitalised patients. Patients aged 75 years and over with pneumonia and hospitalised between 1/1/2013 and 30/6/2013 in the departments of medicine (5) and intensive care (1) of our university hospital were included. Microbiological findings, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…In contrast, AIDS, lung transplantation, asplenia, and aplastic anemia seem to be less frequent at admission and to represent distinct clinical entities. Findings of previous studies seem to be in line with our results, with AIDS patients considered as a distinct patient population and with very few observational studies available on asplenia and aplastic anemia [21,[27][28][29][30][31] In agreement with previous reports, S. pneumoniae is the leading microorganism in both immunocompromised and immunocompetent groups [32,33]. Among pathogens covered by standard CAP therapy, only P. aeruginosa was more frequently isolated in immunocompromised compared with immunocompetent patients.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, AIDS, lung transplantation, asplenia, and aplastic anemia seem to be less frequent at admission and to represent distinct clinical entities. Findings of previous studies seem to be in line with our results, with AIDS patients considered as a distinct patient population and with very few observational studies available on asplenia and aplastic anemia [21,[27][28][29][30][31] In agreement with previous reports, S. pneumoniae is the leading microorganism in both immunocompromised and immunocompetent groups [32,33]. Among pathogens covered by standard CAP therapy, only P. aeruginosa was more frequently isolated in immunocompromised compared with immunocompetent patients.…”
Section: Discussionsupporting
confidence: 92%
“…Though sputum culture is recommended in international guidelines [3,11], it is hard to obtain in elderly patients [12]. Our results compare with those of Putot et al, who were able to collect sputum from only 15% of elderly patients hospitalized for pneumonia [5]. Obtaining more good-quality lower respiratory tract samples would require an invasive procedure [13,14].…”
Section: Discussionsupporting
confidence: 47%
“…The difficulty in obtaining high-quality respiratory samples for microbiological analysis (e.g. sputum cultures) is an important limitation in the elderly [5]. Use of molecular biology technology improves the diagnostic yield in suspected pneumonia and is often prescribed by physicians, but it is unclear how it impacts clinical management [6].…”
Section: Introductionmentioning
confidence: 99%
“…27 Because of the adverse effects of hospitalization there have been increasing demands on nursing homes to reduce hospitalizations, 28 which has resulted in studies to define "potentially avoidable hospitalizations" of nursing home residents. 27À30 Pneumonia is one of the common diagnoses associated 19 Maruyama et al 20 Pulverino et al 21 Ma et al 22 Ewig et al 23 Putot et al 24 with potentially avoidable hospitalizations of nursing home residents. 31 Multiple factors have been identified that result in hospitalization of residents with suspected NHAP: elevated respiratory rate, afterhours evaluation, for-profit facility ownership, severity of illness, radiographic pneumonia, oxygen saturation <90%, and facility resources.…”
Section: Hospitalization Decisionmentioning
confidence: 99%